Analysis of RSTP Synchronization Performance and Its Security Features in Simulation Networks - almagoz, malak; Nuredin Ahmed (AlQalam Journal of Medical and Applied Sciences, 2025)
This study focuses on the design and implementation of an experimental network composed of three interconnected switches in order to analyze the performance of the Rapid Spanning Tree Protocol (RSTP). The protocol was applied to examine its role in preventing switching loops and controlling port states to ensure overall network stability. The network topology and all configurations were implemented using the Cisco Packet Tracer simulation tool, where RSTP was enabled, a root bridge was selected, and access ports were configured using PortFast, BPDU Guard, and Root Guard to improve convergence speed and enhance security. In addition, Root Guard was applied on inter-switch links to preserve the stability of the spanning tree structure. A link failure scenario was simulated to observe the protocol’s behavior during topology changes and to evaluate its ability to quickly restore connectivity through an alternative path. The results demonstrated that RSTP operated efficiently, successfully prevented loop formation, and maintained continuous network stability. Furthermore, the study examined the convergence behavior of RSTP during topology changes caused by link disconnection, confirming its effectiveness in rapidly reconstructing network paths.